Rethinking the Age of Zoo Reform: Review of Lisa Uddin, Zoo Renewal: White Flight and the Animal Ghetto - Ito, Takashi (Humanimalia, 2016)
Lisa Uddin, Zoo Renewal: White Flight and the Animal Ghetto. Minneapolis: University of Minnesota Press, 2014. xi + 277 pp. with 8 color plates. $98 hc; $28 pbk